ANALISA PENGGABUNGAN PERUSAHAAN (BUSINESS COMBINATION) DENGAN MENGELUARKAN SATU JENIS SAHAM MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, - (www.bsi.ac.id, 2016)
Business competition is increasing, demanding the company to continue to develop its business in order to stay ahead again. It is necessary for mutually beneficial cooperation between the company with another company. One form of cooperation that can be taken the company to expand its business is through business combinations (business combination) between the two or more other companies, both similar and dissimilar. There are many types and forms of business combinations, including acquisitions. Acquisition is a form of merger where one company, ie the acquirer (the acquirer) to obtain control over the net assets and operations of the acquired company (acquiree), to provide certain assets, recognizing an obligation, or issuing stock. Development of the company through ownership of the majority of the shares of other companies is a very profitable way. Because the majority of its stocks of other companies, meaning reserves the right to fully control the operation and management of other companies. There are two factors to consider in choosing a base that will be used to determine the contribution of each of the parties to a merger of business entities, namely the incorporation of the company by issuing a type of share capital and incorporation of the company by issuing two or more types of the share capital. Keywords: Merger Company, One Type Shares, Ms. Access Programming